Дослідження залежності щільності деревних брикетів від розміру частинок сировини - Болтянський, Борис Володимирович; Boltianskyi, Borys (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: У статті досліджено вплив фракційного складу деревної тирси на щільність паливних брикетів, отриманих високотемпературним пресуванням. Метою роботи було кількісне обґрунтування раціонального розміру фракції для забезпечення максимального ущільнення. Експерименти проводилися з монофракціями від 2 до 6 мм за фіксованих параметрів пресування 100–110 °C та вологості сировини 8 %. Аналіз результатів показав, що найвища щільність була досягнута з використанням фракції розміром 4 мм. Оптимум пояснюється найкращим балансом між пластичною податливістю й ефективністю укладання, що сприяє якісній термопластичній консолідації лігніну. Встановлено, що використання як надмірно дрібної, так і грубої фракції знижує щільність продукту. /// EN: The article investigates the influence of the fractional composition (particle size) of wood sawdust on the physical density of fuel briquettes obtained by high-temperature pressing. The aim of the work was to quantitatively justify the rational fraction size necessary to ensure the maximum degree of material compaction under a constant technological regime. The experiments were conducted using five clearly defined monofractions of sawdust in the range from 2 to 6 mm. The pressing conditions were strictly fixed: the matrix temperature was 100–110 °C, which corresponds to the conditions for lignin activation, and the moisture content of the raw material was maintained at an optimal level of 8 %. Analysis of the results showed a nonlinear dependence of density on particle size, with a pronounced extremum. The highest density ρ = 1.2 t/m3 was achieved using a fraction size of 4 mm. This optimal fraction size is explained by the achievement of the best balance between the plastic compliance of particles under high pressure of and the efficiency of packing (minimization of voids). It has been established that the use of an excessively fine fraction significantly complicates air removal and increases internal friction, while a coarse fraction of more than 6 mm reduces the density to ρ = 1 t/m3 due to its internal rigidity and insufficient contact area for the formation of a monolithic structure. This confirms that a fraction composition of 4 mm is the critical technological optimum for ensuring high quality thermoplastic consolidation of lignin. The quantitative data obtained can be used to improve the raw material grinding stage on industrial lines. This will minimize the energy costs of grinding and maximize the mechanical stability of the finished biofuel product, as well as formulate practical recommendations for improving quality and competitiveness.
Study of the dependence of the density of wood bricks on the size of raw material particles
Keywords: брикетування; тирса; брикети; лігнін; тиск; вологість; щільність; термомеханічна активація; briquetting; sawdust; briquettes; lignin; pressure; moisture content; density; thermo mechanical activation